Increasing Tourist Arrivals: Do Capital Investment and Government Spending Matter? Array - Jeje, Kafigi (The Journal of Accounting and Management, 2021)
The contribution of tourism sector on economic growth has been noticed in many economies around the globe. Countries strive to improve their tourism sectors by employing strategies that seek to attract a sizable amount of tourist arrivals. Literature suggests that both capital investment in travel and tourism, and government spending on travel and tourism service are crucial factors in promoting the competitiveness of the sector. However, little is known as whether the two factors influence the number of arrivals. Therefore, this study sought to establish the contribution of both government spending and capital investment in influencing tourist arrivals. The study employed data from 150 countries focusing on the years 2010 to 2018. Based on the multiple regression analysis, this study confirms that there exist positive linear relationships between number of arrivals and capital investment in travel and tourism for the years 2010 to 2018. Nevertheless, the study finds that government spending does not influence the number of arrivals. Therefore, governments need to study and understand the interconnectedness between government spending and capital investment in order to carefully allocate their resources in advancing the competitiveness of the investment climate of their respective tourism sectors.